Problematika Pembelajaran Daring pada Mata Pelajaran PAI Siswa Kelas XI di SMKN 1 Lingsar Tahun Pelajaran 2020/2021 - Muhammad Yuslih; Nuralip (QuranicEdu: Journal of Islamic Education, 2022)
The emergence of the Covid-19 pandemic forced the learning process to be carried out online. Learning with the online system caused various problems in it, there was no learning in PAI subjects for class XI at SMKN 1 Lingsar. Therefore, this paper aimed to show the various problems contained in the online learning process, as well as the efforts made to overcome these problems. This research was included in the category of field research with analytical descriptive method. So the data sources in this research were PAI teachers, school principals, and class XI students of SMKN 1 Lingsar. To obtain valid data in this research, researchers used the interview method, and observation in data collection. The research results indicated that there were several problems faced by teachers and participants in the online learning process including, not a few students who did not understand the material, lack of cooperation between educators and parents of students, difficulties in determining methods, difficulties in evaluation, students who were less active, and inadequate internet access. Then the efforts made include simplifying the material, increasing cooperation, varying the method according to the material, conducting evaluations according to the plan, collaborating with homeroom teachers, BK teachers so that students were more active, and providing quotas to students.